2012
DOI: 10.3109/13693786.2011.603367
|View full text |Cite
|
Sign up to set email alerts
|

Multiple subcutaneous cysts due toExophiala spiniferain an immunocompetent patient

Abstract: Here we report a case of a 55-year-old Indian male presenting with multiple subcutaneous cysts, which developed from painful nodules at the dorsal right wrist joint. Subsequently a painful nodule appeared on the left knee joint. Cytological examination of the knee swelling revealed a suppurative inflammatory lesion consisting of neutrophils, lymphocytes, multinucleated giant cells and few fungal elements, without involvement of the overlying skin. Exophiala spinifera was cultured (CBS 125607) and its identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Some cases (Rajam et al, 1958 ; Barba-Gomez et al, 1992 ; Padhye et al, 1996 ; Develoux et al, 2006 ; Tomson et al, 2006 ; Srinivas et al, 2016 ) were reported as chromoblastomycosis, although typical muriform cells were mostly lacking. Fatal systemic infections are known; 36 cases have been recorded in English and Chinese literature (Rajam et al, 1958 ; Nishimura and Miyaji, 1983 ; Padhye et al, 1983 , 1984 ; Mirza et al, 1993 ; Campos-Takaki and Jardim, 1994 ; de Hoog et al, 1999 ; Rajendran et al, 2003 ; Negroni et al, 2004 ; Dutriaux et al, 2005 ; Baubion et al, 2008 ; Singal et al, 2008 ; Fothergill et al, 2009 ; Harris et al, 2009 ; Radhakrishnan et al, 2010 ; Li et al, 2011 ; Badali et al, 2012 ; Daboit et al, 2012 ; Lin et al, 2012 ; Bohelay et al, 2016 ; Silva et al, 2017 ; Table 2 ). Among the 12 systemic infections, all cases concerned immunocompetent patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases (Rajam et al, 1958 ; Barba-Gomez et al, 1992 ; Padhye et al, 1996 ; Develoux et al, 2006 ; Tomson et al, 2006 ; Srinivas et al, 2016 ) were reported as chromoblastomycosis, although typical muriform cells were mostly lacking. Fatal systemic infections are known; 36 cases have been recorded in English and Chinese literature (Rajam et al, 1958 ; Nishimura and Miyaji, 1983 ; Padhye et al, 1983 , 1984 ; Mirza et al, 1993 ; Campos-Takaki and Jardim, 1994 ; de Hoog et al, 1999 ; Rajendran et al, 2003 ; Negroni et al, 2004 ; Dutriaux et al, 2005 ; Baubion et al, 2008 ; Singal et al, 2008 ; Fothergill et al, 2009 ; Harris et al, 2009 ; Radhakrishnan et al, 2010 ; Li et al, 2011 ; Badali et al, 2012 ; Daboit et al, 2012 ; Lin et al, 2012 ; Bohelay et al, 2016 ; Silva et al, 2017 ; Table 2 ). Among the 12 systemic infections, all cases concerned immunocompetent patients.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic intraspecific variation was found e.g., in protease, urease and acid production, but none of these parameters could be linked (Table 3 ). Antifungal susceptibility shows some variability in both species (Badali et al, 2012 ), and this could not be linked to other types of variation either. Given the rather significant variation in susceptibility, it is recommended always to perform in vitro prior to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous swellings in phaeohyphomycosis are easily amenable to fine needle aspiration cytology, which serves as a rapid diagnostic tool enabling the timely administration of antifungal agents. A literature search showed a relative paucity of publications, largely limited to case reports on the cytomorphology of phaeohyphomycosis [4-6]. The present study was undertaken to establish the role of cytology in diagnosing phaeohyphomycosis and to further discuss potential diagnostic pitfalls and differential diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although limited data on the number of cases occurring are available and the epidemiology of airways infections caused by E. jeanselmei is poorly documented. Inside buildings, the way of contamination by this species is presumably linked to water reservoirs of air-conditioning units or pipings (Badali et al 2012 ; Wang et al 2001 ). As this species can cause health problems, its monitoring is needed.…”
Section: Introductionmentioning
confidence: 99%
“…For E. jeanselmei , these ITS regions offer the possibility to develop molecular tools to discriminate the species, even inside the E. spinifera clade (Wang et al 2001 ; Woo et al 2013a ; Zeng and De Hoog 2008 ). Despite these previous studies investigating the E. jeanselmei genotype (Badali et al 2012 ; Kawasaki et al 2005 , 1999; Woo et al 2013a ), molecular tools for the specific detection of this fungus are however still poorly documented.…”
Section: Introductionmentioning
confidence: 99%